2020
DOI: 10.4103/ijo.ijo_2078_19
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment alterations in congenital primary aphakia—a clinicopathologic report of five cases

Abstract: Purpose: To report the clinicopathological features of corneal buttons in patients with congenital primary aphakia. Methods: Five corneal specimens of five patients with congenital primary aphakia who underwent penetrating keratoplasty (PKP) were studied by light microscopy, and immunohistochemistry with anti-smooth muscle (SMA) antibody. Results: All patients were born from consanguineous parents. Of the five, two patients were identical twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Given dense corneal opacities, full clinical assessment of FOXE3 defects requires alternative imaging modalities, such as ultrasound, optical coherence tomography (OCT), or magnetic resonance imaging (MRI) to diagnose; thus, the complete spectrum of FOXE3 ocular defects in many affected individuals may not be fully identified. In prior studies, all individuals with primary aphakia undergoing penetrating keratoplasty were found to have atrophic iris tissue, suggesting that the absence of the lens disrupts iris development; however, since no genetic analysis was performed, the causative variant(s) in these cases may directly affect development of both structures ( 40 ). Indeed, mouse models ( dysgenic lens , Foxe3 dyl ) support a role for Foxe3 in iris development; Foxe3 +/− mice have intact lens epithelia but hypoplastic iris tissue and iridocorneal and iridolenticular adhesions ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given dense corneal opacities, full clinical assessment of FOXE3 defects requires alternative imaging modalities, such as ultrasound, optical coherence tomography (OCT), or magnetic resonance imaging (MRI) to diagnose; thus, the complete spectrum of FOXE3 ocular defects in many affected individuals may not be fully identified. In prior studies, all individuals with primary aphakia undergoing penetrating keratoplasty were found to have atrophic iris tissue, suggesting that the absence of the lens disrupts iris development; however, since no genetic analysis was performed, the causative variant(s) in these cases may directly affect development of both structures ( 40 ). Indeed, mouse models ( dysgenic lens , Foxe3 dyl ) support a role for Foxe3 in iris development; Foxe3 +/− mice have intact lens epithelia but hypoplastic iris tissue and iridocorneal and iridolenticular adhesions ( 41 ).…”
Section: Discussionmentioning
confidence: 99%